Analisis Efek Doppler Dalam Sistem Radar Dan Telekomunikasi - Harefa, Dhealova Angelica; Mendrofa, Aroli (CV. SINAR HOWUHOWU, 2025)
The Doppler effect is a phenomenon of frequency shift caused by relative motion between a wave source and receiver, with significant applications in radar and telecommunication systems. This study conducts a systematic literature review to explore its utilization in these fields. In radar systems, the Doppler effect is essential for target detection, speed measurement, and classification. In telecommunication systems, it supports channel estimation, time synchronization, and interference reduction. Despite its advantages, challenges such as multipath propagation and high-speed movement require further attention to enhance system performance and reliability.